Immunotargeting of Integrin αβ for Single-Photon Emission Computed Tomography and Near-Infrared Fluorescence Imaging in a Pancreatic Cancer Model - Winn Aung MBBS, PhD; Atsushi B. Tsuji PhD; Hitomi Sudo PhD; Aya Sugyo M.Ed; Takako Furukawa PhD; Yoshinori Ukai PhD; Yoshikazu Kurosawa PhD; Tsuneo Saga MD, PhD (Molecular Imaging)
To explore suitable imaging probes for early and specific detection of pancreatic cancer, we demonstrated that α 6 β 4 integrin is a good target and employed single-photon emission computed tomography (SPECT) or near-infrared (NIR) imaging for immunotargeting. Expression levels of α 6 β 4 were examined by Western blotting and flow cytometry in certain human pancreatic cancer cell lines. The human cell line BxPC-3 was used for α 6 β 4 -positive and a mouse cell line, A4, was used for negative counterpart. We labeled antibody against α 6 β 4 with Indium-111 ( 111 In) or indocyanine green (ICG). After injection of 111 In-labeled probe to tumor-bearing mice, biodistribution, SPECT, autoradiography (ARG), and immunohistochemical (IHC) studies were conducted. After administration of ICG-labeled probe, in vivo and ex vivo NIR imaging and fluorescence microscopy of tumors were performed. BxPC-3 tumor showed a higher radioligand binding in SPECT and higher fluorescence intensity as well as a delay in the probe washout in NIR imaging when compared to A4 tumor. The biodistribution profile of 111 In-labeled probe, ARG, and IHC confirmed the α 6 β 4 specific binding of the probe. Here, we propose that α 6 β 4 is a desirable target for the diagnosis of pancreatic cancer and that it could be detected by radionuclide imaging and NIR imaging using a radiolabeled or ICG-labeled α 6 β 4 antibody.